Exploration of the Brazilian Term Structure in a Hidden Markov Framework - Munclinger, Richard (IMF Working Papers; Working Paper, 2011)
We apply a hidden Markov model of the term structure to modeling the Brazilian swap rate curve. We examine the model's characteristics and its performance in describing the cross-sectional and time-series dynamics of the term structure. Two regimes are identified, a high level and a high volatility regime and a low level and low volatility regime. Both regimes are persistent and are explained by the level and the slope of the term structure. The model is estimated using a Bayesian MCM algorithm that produces consistent standard errors and a reliable method for testing the differences between the model parameters.